Prevalence of Current Restless Legs Syndrome Symptoms Among Patients Treated with Buprenorphine/Naloxone for Opioid Use Disorder - Wipper B; Cooke MP; Winkelman JW (Nature and Science of Sleep, 2023)
Benjamin Wipper,1,2 Michelle Pearl Cooke,3 John W Winkelman1,2 1Sleep Disorders Clinical Research Program, Massachusetts General Hospital, Boston, MA, USA; 2Department of Psychiatry, Harvard Medical School, Boston, MA, USA; 3Substance Use Disorder Services, Lemuel Shattuck Hospital, Jamaica Plain, MA, USACorrespondence: John W Winkelman, Tel +1617 643-9101, Fax +1617 724-6513, Email jwwinkelman@mgh.harvard.eduObjective: The purpose of this study was to determine the prevalence of Restless Legs Syndrome (RLS) in patients with Opioid Use Disorder (OUD) taking buprenorphine/naloxone maintenance therapy, and to assess symptom frequency, severity, and sleep disruption due to RLS.Methods: Surveys inquired about demographic information, amount of time on maintenance treatment, previous drug use, current prescribed medications and alcohol use, and RLS symptoms. Participants were determined to have definite, probable, possible, or no RLS symptoms based on pre-established criteria from the Cambridge-Hopkins Questionnaire.Results: The sample (n=129) was 33.3% female, 81.5% white, and the mean age was 40.6 years (SD=11.9). The median duration of buprenorphine/naloxone use was 3 years. 13.2% of participants had definite/probable RLS symptoms; these symptoms tended to be of moderate severity, occur at least 5– 15 times a month, and disrupt sleep to a moderate degree. Of the 17 participants with definite/probable RLS symptoms, just four were taking a medication commonly used to alleviate RLS. An additional 7.0% had possible RLS symptoms.Conclusion: Relatively high rates of current RLS symptoms were observed; the prevalence of clinically significant RLS was notably higher than that seen in the general population or in previously assessed clinical populations. RLS is common in those acutely withdrawing from opioids, and our data demonstrate that these symptoms are present in a sizable portion of patients on OUD maintenance therapy. Most patients with definite/probable current RLS symptoms did not report taking prescribed medications that have established efficacy for RLS.Keywords: opioid use disorder, restless legs syndrome, maintenance therapy, buprenorphine, sleep disorders